Fast and precise data acquisition for broadband microwave tomography systems. (21st August 2017) - Mallach, Malte; Musch, Thomas
Abstract: Microwave imaging (MWI) is a noninvasive diagnosis method, which has been investigated for a wide range of applications. MWI techniques include radar-based approaches as well as microwave tomography (MWT). One major challenge designing broadband MWI systems is the development of a data acquisition unit that allows for fast broadband scattering parameter measurements with a high measurement precision and a high dynamic range (DR), at reasonable cost. The cost-performance criteria cannot readily be achieved using commercial, continuous wave (CW) vector network analyzers (VNA) or pulse-based systems. Therefore, in this paper we propose a data acquisition unit, based on the well-known method of frequency modulated continuous wave (FMCW) network analysis. It offers fast scattering parameter measurements without compromising the measurement precision and the DR, and is particularly advantageous for MWI systems requiring a high number of frequency samples. A 2-port metadyne prototype electronics with low hardware complexity was developed, which allows very fast, precise, and accurate reflection and transmission measurements in the frequency range from 0.5 GHz to 5.5 GHz. To the best of the authors' knowledge, a system with combined performance in terms of bandwidth, sweep time (1 ms), DR (80 dB) and maximum signal-to-noise-and-spurious ratio (65 dB) has not previously been reported. The design, the calibration, and the characterization of the prototype electronics are described in detail, and the measurement results are compared to those obtained with commercial high-end CW VNA. The advantages and limitations of the metadyne FMCW technique compared to the heterodyne CW technique are discussed. The applicability of the prototype electronics and the described calibration technique for microwave imaging has been demonstrated based on measurements using an 8-port MWT sensor and a switching matrix.